T cell repertoire scanning is promoted by dynamic dendritic cell behavior and random T cell motility in the lymph node - Miller, Mark J. (National Academy of Sciences, 2004)
Dendritic cells (DCs) ingest antigens in peripheral tissues and migrate to lymph nodes where they present MHC class II-bound antigen to CD4(+) T cells. We used two-photon microscopy to image the single-cell dynamics of interactions between DCs and T cells within intact lymph nodes in the absence of relevant antigen. DCs were fluorescently labeled in vivo by cutaneous injection of alum adjuvant including carboxyfluorescein diacetate succinimidyl ester (CFSE). CFSE-positive DCs (CD11c(+), CD11b(+), and low-to-intermediate CD8(+)) were observed in draining lymph nodes 24–72 h later. Labeled DCs meandered slowly (2–3 μm·min(–1)) in the T cell zone near B cell follicles but vigorously extended long agile dendrites. Encounters between T cells and DCs arose as T cells moved autonomously along random paths. Moreover, T cells did not accumulate around DCs, and their relative velocities approaching and departing DCs were equivalent, implying that T cells are not attracted toward DCs by chemotactic gradients but rather encounter them by chance. T cell/DC contacts occurred primarily on dendrites at arm's length from the DC soma and typically lasted ≈3 min, enabling an individual DC to interact with up to 5,000 T cells per hour. We conclude that dynamic DC gesticulation and random T cell motility together enhance the stochastic scanning of the T cell repertoire, thereby enabling rapid initiation of the immune response.